Sensitivity of tumor versus normal cell migration and morphology to cold atmospheric plasma‐treated media in varying culture conditions. Issue 2 (11th November 2019) - Pranda, Marina A.; Murugesan, Brittney J.; Knoll, Andrew J.; Oehrlein, Gottlieb S.; Stroka, Kimberly M.
Abstract: Cold atmospheric plasma (CAP) produces reactive oxygen species and reactive nitrogen species, which may disproportionally damage tumor cells, resulting in potentially selective cancer therapy. Here, we compare the effects of two CAP sources, that is, the atmospheric pressure plasma jet and the surface micro discharge, on the selectivity of CAP‐treated cell‐culture media. CAP‐treated media were applied to metastatic breast tumor cells and their normal breast epithelial cell counterparts to assess treatment selectivity, while systematically varying common cell‐culture media and cell‐matrix binding moieties. We show that media compositions are crucial in a CAP‐treated media selectivity, while binding moieties (specifically, collagen I, fibronectin, and poly‐d ‐lysine) play a lesser role. These data have further implications in the translation of CAP to in vivo use. Abstract : Cold atmospheric plasma (CAP) as a cancer therapeutic has to be optimized to particular experimental conditions to be successful in vivo . We show that the selectivity of CAP is highly sensitive to treatment type (atmospheric pressure plasma jet vs. surface micro discharge) and length, as well as, cell‐culture media. It is less sensitive to varying cell‐binding moieties.